The appreciation of political works of art: The example of "Triumph of the Will" - Bannister, Randee (University of Ottawa (Canada), 2004)
The question that we are considering is how to appreciate artworks that have not only an aesthetic presence but a political side as well. We feel that this question is necessary to consider because in order to have a full appreciation of an artwork it is important to consider all facets of the work, but also refrain from including considerations that are not necessary to include. In order to explain why this question is important and also to show a potential response, we use the example of Leni Riefenstahl's film Triumph of the Will. This film is a perfect example of how the aesthetic and political can combine in art. Other suggestions of how to have a complete appreciation of this film, as we try to show, are insufficient as an answer to our question and so we propose our own theory of the appreciation of not just political artworks but all artworks, that being partial autonomy.
Keywords: Philosophy.